The diagnostic value of immunohistochemically HBsAg staining patterns in chronic hepatitis B infection: correlation among histological, serological and immunohistochemical findings - Selçuk BİLGİ and İsmail ÇIRPAN and Kemal KUTLU and Sedat ÖZDEMİR and; in DÖKMECİ (Turkish Journal of Gastroenterology, 2020)
-